Solve the differential equation: ydx+(x-y ^{ 2 } )dy=0
CBSE Class 12 Sample Paper for 2023 Boards
Question 2 Important
Question 3
Question 4 Important
Question 5
Question 6 Important
Question 7
Question 8 Important
Question 9
Question 10 Important
Question 11 Important
Question 12
Question 13 Important
Question 14 Important
Question 15
Question 16
Question 17 Important
Question 18 Important
Question 19 [Assertion Reasoning] Important
Question 20 [Assertion Reasoning] Important
Question 21 (Choice 1) Important
Question 21 (Choice 2)
Question 22
Question 23 (Choice 1)
Question 23 (Choice 2) Important
Question 24 Important
Question 25
Question 26 Important
Question 27 (Choice 1) Important
Question 27 (Choice 2)
Question 28 (Choice 1)
Question 28 (Choice 2) Important
Question 29 (Choice 1) Important You are here
Question 29 (Choice 2) Important
Question 30
Question 31 Important
Question 32 Important
Question 33 (Choice 1)
Question 33 (Choice 2) Important
Question 34 (Choice 1) Important
Question 34 (Choice 2) Important
Question 35
Question 36 (i) [Case Based] Important
Question 36 (ii)
Question 36 (iii) (Choice 1) Important
Question 36 (iii) (Choice 2)
Question 37 (i) [Case Based] Important
Question 37 (ii)
Question 37 (iii) (Choice 1)
Question 37 (iii) (Choice 2) Important
Question 38 (i) [Case Based] Important
Question 38 (ii)
CBSE Class 12 Sample Paper for 2023 Boards
Last updated at April 16, 2024 by Teachoo
Question 29 (Choice 1) Solve the differential equation: π¦ππ₯+(π₯βπ¦^2 )ππ¦=0 For equation π¦ππ₯+(π₯βπ¦^2 )ππ¦=0 We observe that we cannot use variable separation method Letβs try to put in the form π π/π π + Py = Q or π π/π π + P1 x = Q1 Now, y dx + (x β y2) dy = 0 y dx = β (x β y2)dy π π/π π = (βπ)/(πβπ^π ) This is not of the form ππ¦/ππ₯ + Py = Q Thus, letβs find π π/π π ππ₯/ππ¦ = (π¦^2 β π₯)/π¦ ππ₯/ππ¦ = y β π₯/π¦ π π/π π + π/π = y Comparing with π π/π π + P1 x = Q1 β΄ P1 = 1/π¦ &. Q1 = y Finding Integrating factor, IF = π^β«1βγπ1 ππ¦γ = π^β«1βππ¦/π¦ = π^πππβ‘π = y Solution is x (IF) = β«1βγ(πΈπ Γ π°π)π π+πγ π₯π¦=β«1βγπ¦ Γ π¦ ππ¦+πγ ππ= β«1βγπ^π π π+πγ ππ= π^π/π+πͺ